The Lands and Trust Services Initiative: Its Potential Impact on the Federal Government's Fiduciary Obligations - McNeil, Kent (Osgoode Digital Commons, 2000)
This is a research report prepared for the Assembly of First Nations, Ottawa. Part I (August, 1998: 64 pages), Part II (December, 1999: 67 pages), Appendix (June, 2000: 34 pages).